Combined in situ synchrotron micro X-ray diffraction and high-speed imaging on rapidly heated and solidified Ti–48Al under additive manufacturing conditions. (15th March 2016) - Kenel, C.; Grolimund, D.; Fife, J.L.; Samson, V.A.; Van Petegem, S.; Van Swygenhoven, H.; Leinenbach, C.
Abstract: An in situ method to study the behavior of alloys during rapid heating and cooling combining laser heating with synchrotron micro X-ray diffraction and high-speed imaging is presented. Near-spherical Ti–48Al specimens were melted using a laser-based heating system consisting of two diode lasers and subsequently rapidly solidified using a Cu support structure. The Al-rich Ti–48Al forms a fine grained dual phase α2  + γ microstructure. Upon solidification, the formation of the β-phase is fully suppressed. Time-resolved peak evolution and temperature-corrected micro X-ray diffraction data provides clear observations of solidification and solid state phase transformations under non-equilibrium conditions similar to beam-based additive manufacturing. Graphical abstract: